Liquidity Variation and the Cross-Section of Stock Returns - FU, Fangjian (Institutional Knowledge at Singapore Management University, 2012)
Stock liquidity varies substantially over time. A significant decrease in liquidity is often followed by a sizable rebound, and vice versa. The month-to-month liquidity change predicts the cross-sectional stock returns in the following month. Caeteris paribus, a liquidity decrease predicts a low return and a liquidity increase predicts a high return. The results are not explained by other cross-sectional return determinants including the liquidity level. The results are consistent with the mean-reverting nature of liquidity and its variation being priced. A liquidity reduction predicts an expected liquidity increase and thus a lower expected return, and vice versa. Our research suggests liquidity variation as an important factor of asset pricing. Its effect is independent from the widely documented liquidity level effect.